AIDS PANDEMIC: THE VOICE OF THE YOUTH IN THE KISWAHILI NOVEL - Amukowa, Deborah N. (European Scientific Journal, ESJ, 2012)
It is argued that there is little agreement among the youth about how the continuity of life can be maintained and what order should be created or restored concerning their health. So long as the world is rapidly changing and affects the way the youth think about themselves, it is claimed that a parallel change should be realized to empower the youth and enable them to positively solve their health problems. Empowering the youth to independently address their health matters is central to having them voice their opinions through literary works. This paper looks at the Aids pandemic through the voice of the youth in the Kiswahili novel. This study explores the value of empowering the youth to fight AIDs pandemic and recommends that the focus be shifted to them not only in fighting the AIDs epidemic, but also becoming successful individuals who are confident of themselves as well as being capable of contributing to the development of their society